Nature of war in the Information Age : Clausewitzian future - Lonsdale, David J. (Portland, OR : Frank Cass, 2004)
Will the information age witness a transformation in the nature of war? Putting the notion to the test, the author uses a range of contexts to assess whether the Clausewitzian nature of war will retain its validity.
Includes bibliographical references and index.
Keywords: 2000-2099; War; Information warfare; World politics -- 21st century; Information warfare; War; World politics